The Effectiveness of Counselling on the Importance of Fe Tablets to the Motivation to Meet the Fe Needs - Ulfa, Maria; Wibisono, Wahyu (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
In the period of 2018 maternal bleeding occurred 15% of a total of 40 mothers who then carried out referrals to the hospital due to lack of iron supplements during pregnancy. Lack of knowledge, attitudes, actions of pregnant women are not good, side effects in tablets can lead to someone less to comply with the advice. The design in this research was pre-experimental design used pretest-posttest design approached. The sample consists of 150 correspondences selected by purposive sampling technique. Data obtained by reviewing the motivation of pregnant women before counseling, after counseling, and reviewed the motivation of pregnant women after counseling. This research used statistical test wilxocon sign rank test and assisted using SPSS For Windows. The result showed that the motivation before counseling was 6,7% high, 80,0% medium and 13,3% low. After motivation counseling to be 80.0% high, 20.0% medium and 0% low. Based on the results of the analysis using statistical test wilxocon sign rank test obtained p value = 0,000, so p value = 0,000 < α = 0.05 so that counseling conducted affect the motivation of pregnant women in drinking regularity Fe. From the results of the research, pregnant women are expected to further increase knowledge about Fe in order to increase the motivation of taking Fe tablets.